Coordinating conjunction in students’ recount text: A sentence construction analysis - Natalia Anggrarini; Indra Yoga Prawiro; Melawati Melawati (Concept : Community Concern for English Pedagogy and Teaching, 2023)
This study sought to examine student errors in employing a coordinating conjunction to produce recall text. This study found all errors in 36 recount texts written by senior high school students in Indramayu (district in West Java) using Halliday and Hasan's Taxonomy (1976) and Ong's framework (2011) about the errors in using conjunction: misuse, unnecessary addition, omission, and repetition of conjunction. The results describe the condition of the students: they overgeneralized the use of coordinating; they also lacked understanding in terms of sentence construction due to limited knowledge of particular conjunctions and the function of coordinating conjunctions, which led to the incomplete application of rules in sentences. A comprehensive explanation of conjunction is needed when teaching writing to students. The students should clearly understand each function of conjunction to produce a meaningful text. Some limitations are provided along with suggested directions for future research to get a deeper and wider perspective in a similar context. Keywords: Recount text; conjunction; error analysis; sentence construction